Tits Alternative for $2$ -dimensional $CAT(0)$ complexes. (16th December 2022) - Osajda, Damian; Przytycki, Piotr
Abstract: We prove the Tits Alternative for groups acting on $2$ -dimensional $CAT(0)$ complexes with a bound on the order of the cell stabilisers.